Research into cemented paste backfill properties and options for its application: Case study from a Kryvyi Rih Iron-ore Basin, Ukraine - Petlovanyi, Mykhailo; Sai, Kateryna (Mining of Mineral Deposits, 2024)
Purpose. The purpose is to conduct experimental research on a set of properties of cemented paste backfill mass based on a number of natural-technogenic materials of the Kryvyi Rih Iron-ore Basin with the aim of its further use in technologies for restoring a heavily disturbed earth's surface by complex iron ore mining. Methods. A comprehensive toolkit is used: X-ray fluorescence and X-ray diffraction analyses to study the chemical and mineralogical composition of the components, conductometer measurements of the electrical conductivity of the mixtures during their hardening, laboratory studies of the formulations of paste backfill mixtures and determination of their physical-mechanical characteristics using a laboratory hydraulic press, an analytical study to determine suitable regions for paste backfilling, taking into account the presence of technogenic cavities, tailings dumps and binder materials. Findings. It has been found that a paste-like homogeneous state of the backfill mixture using iron ore beneficiation tailings from mining and processing plants of Ukraine is achieved at a solid part content of about 73-75%, which provides an optimal balance between its flowability and mechanical strength. A set of patterns of strength changes depending on the binder material dosage, solid part content and hardening period for paste backfill mixture based on pure cement and with different variations of alternative binder materials has been determined. The patterns have been revealed of the correlation between the paste backfill mixture strength and the electrical conductivity parameters. Originality. A method for predicting the early and late strength of paste backfilling has been developed, based on the identified patterns between the electrical conductivity of the paste mixture, the time to reach its peak, and the strength at different stages of hardening. The knowledge and understanding of the physical-mechanical properties of cemented paste backfill mixture in the conditions of hardening under the influence of climatic environmental conditions have been further developed. Practical implications. The conducted research on the properties of paste backfilling is useful for designing a technology for restoring heavily disturbed earth’s surface, namely, backfilling of failure zones of the earth’s surface from the influence of iron ore mines, backfilling of identified underground unfilled cavities of closed mines and mined-out spaces of closed quarries. A concept for implementing a paste backfilling in the western part of the city of Kryvyi Rih has been developed, which is expected to contribute to the environmental, economic and social development of the region.